Impaired flow-mediated dilation response and carotid intima-media thickness in patients with type 1 diabetes mellitus with a mean disease duration of 4.1 years - Tacito, Lúcia Helena Bonalume; Pires, Antonio Carlos; Yugar-Toledo, Juan Carlos (Archives of Endocrinology and Metabolism, 2017)
This study aimed at assessing the endothelial function in patients with Type 1 diabetes (T1DM) using flow-mediated dilation (FMD) response and carotid artery intima-media thickness (CIMT). This study enrolled 32 T1DM patients (mean disease duration 4.1 years) and 28 age-matched controls (CTL Group). Endothelial function and CIMT were assessed with high-resolution ultrasound using standardized offline measurements. FMD was significantly lower in patients in the T1DM Group (8.9 ± 3.2%) compared with those in the CTL Group (13.3 ± 4.3%; P-value < 0.0001). Similarly, CIMT differed significantly between T1DM patients (0.525 ± 0.03 mm) and controls (0.508 ± 0.03 mm; P-value = 0.041). Even though, the values are within the normal range for age. Patients with T1DM have impaired endothelial function characterized by reduced FMD when compared to controls. However, vascular remodeling as seen by increases in CIMT was not found in this study.